Osobennosti aktivnosti fermentov syvorotki krovi u sportsmenov i netrenirovannych lic - Fomin, N. A.; Gorochov, N. M.; Timoscenko, L. V. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
The purpose of the research was to reveal the features of the intensity of metabolism at athletes of different specializations and unexercised persons, as one of the kinds of markers of development of a long-term adaptation to specific kinds of sports activity.